Parental Knowledge, Attitudes, and Practices Regarding Early Childhood Caries in Bihor, Romania: A Cross-Sectional Study - Abel Emanuel Moca; Raluca Iulia Juncar; Rahela Tabita Moca; Mihai Juncar; Rebeca Daniela Marton; Luminița Ligia Vaida (MDPI AG, 2024)
Background/Objectives: Early childhood caries (ECC) is a significant global health issue, particularly affecting deciduous teeth in young children. ECC is prevalent in Romania, where nearly half of children experience dental caries. This study aimed to assess the influence of gender, age, and living environment on parents' knowledge, attitudes, and practices (KAP) regarding ECC in Bihor County, Romania, using a KAP-type questionnaire. Methods: A cross-sectional study was conducted between March and September 2024, utilizing an online KAP questionnaire distributed via social networks. The sample comprised 419 parents of children under six years old. Respondents provided socio-demographic data and answered questions regarding their knowledge, attitudes, and practices concerning ECC prevention, treatment, and oral health. Statistical analysis was conducted using Chi-square tests to assess associations between demographic factors and parental KAP. A p-value of less than 0.05 was considered statistically significant. Results: Of the 419 respondents, 83.1% were female, and 62.5% were between the ages of 31 and 40. Significant gender-based differences were found in knowledge about pain from caries (93.7% of female participants vs. 81.7% of male participants, p = 0.004) and the importance of brushing twice daily (93.7% of female respondents vs. 80.3% of male respondents, p = 0.010). Younger parents (aged 18-30) were more likely to affirm the effectiveness of fluoride (65.4%) compared to those aged 31-40 (53.1%, p = 0.02). Urban parents were more likely to correctly identify the timing of tooth eruption (59.1% vs. 52.6% of rural parents, p = 0.021). Conclusions: The study highlights gender, age, and urban-rural disparities in parental knowledge and attitudes towards ECC. These findings underscore the need for targeted educational interventions to improve oral health outcomes and reduce ECC prevalence in the Bihor region. Tailored public health strategies addressing demographic factors could enhance preventive oral health behaviors and reduce the healthcare burden associated with untreated dental caries.